TNI Influence Operation and Information Warfare Force; Noopolitik Perspective - Maulaya, Mahbi; Wafi, Fadhlil (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2025)
The news about the Indonesian National Army’s, or Tentara Nasional Indonesia (TNI), budget for internet buzzers has led to public disapproval. This disagreement shows how the public is still unfamiliar with the idea that Influence Operations and Information Warfare (IOIW) is now a thing in national security and defense strategy. This article aims to make sense of why TNI should consider the IOIW capability. With the library research method, this article introduces the conceptual and theoretical argument of Noopolitik and IOIW to the Indonesian policymakers and the general public. Noopolitik is a concept explaining the existence of the noosphere, a world "thinking circuit" and "realm of the mind" that politicians today, in the era of advanced information and communication technology, also consider. Thus, Noopolitik allows us to rationalize that a country nowadays should consider not only the geosphere for its national interest but also the noosphere which one country may hijack and influence through information dissemination. Thus, the noosphere is now a new emergent battlefield, and IOIW refers to the combat that takes place on it, with the goal of gaining influence using information as a weapon. With that idea, this article argues that it is reasonable for TNI to procure the capability for IOIW. The IOIW ability will allow TNI to protect the Indonesian Noosphere from the attacks of its potential adversaries, as they might want to influence Indonesian public opinion and action in a hostile outcome for the nation's harmony and stability. The general public have to grasp the theoretical framework of Noopolitik, which elucidates the contemporary relevance of IOIW. It will lead them to have necessary understanding why should they provide support to TNI for the procurement of additional power for IOIW capabilities when required. This article may function as an initial evaluation for politicians and the public to recognize TNI's augmentation of the IOIW force.